Determinants of Business Performance of Pottery Artisans in Banyumulek Village, West Lombok, Indonesia - Nur Awwalunnisa; Ulfatun Hasanah (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2022)
Purpose: This study aims to determine the factors that affect the business performance of pottery artisans in Banyumulek village, West Lombok Regency. Method: This is associative research employing the sample survey method. The population of the study is the members of Banyumulek Arts Market, as many as 94 artisans from which 48 members are taken samples based on Slovin Formula. Data is analyzed using multiple linear regression while the hypothesis is examined with T-test and F-test processed with SPSS 26. Result: the authors found that the variables of entrepreneurial characteristics have a significant influence partially or simultaneously on the business performance of pottery artisans in Banyumulek Village. The Standardized Coefficient Beta value shows that the future-oriented variable is the most dominant in the business performance of pottery artisans in Banyumulek Village, West Lombok. Contribution: Practically, this research is expected to be helpful for the development of entrepreneurs in West Nusa Tenggara Province, especially in improving the business performance of pottery artisans in Banyumulek Village.